2021
DOI: 10.1101/2021.01.22.427743
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The limits of evolutionary convergence in sympatry: reproductive interference and historical constraints leading to local diversity in warning traits

Abstract: Mutualistic interaction between defended species is a striking case of evolutionary convergence in sympatry, driven by the increased protection against predators brought by mimicry. However, such convergence is often limited: sympatric defended species frequently display different or imperfectly similar warning traits. The phylogenetic distance between sympatric species may indeed prevent evolution towards the exact same signal. Moreover, warning traits are also implied in mate recognition, so that trait conve… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 91 publications
(153 reference statements)
0
5
0
Order By: Relevance
“…Females deceived by the colour pattern then need to deploy substantial efforts to avoid the heterospecific mating. Theoretical studies highlight that RI promotes the evolution of females preference different from the phenotype of the other sympatric species because it reduces the number of costly sexual interactions [McPeek and Gavrilets, 2006, Yamaguchi and Iwasa, 2013, Maisonneuve et al, 2021]. These females preference, caused by RI may therefore explain the evolution of sexual dimorphism in mimetic species [Yamaguchi and Iwasa, 2013].…”
Section: Introductionmentioning
confidence: 99%
“…Females deceived by the colour pattern then need to deploy substantial efforts to avoid the heterospecific mating. Theoretical studies highlight that RI promotes the evolution of females preference different from the phenotype of the other sympatric species because it reduces the number of costly sexual interactions [McPeek and Gavrilets, 2006, Yamaguchi and Iwasa, 2013, Maisonneuve et al, 2021]. These females preference, caused by RI may therefore explain the evolution of sexual dimorphism in mimetic species [Yamaguchi and Iwasa, 2013].…”
Section: Introductionmentioning
confidence: 99%
“…2020) that may impede divergence from the ancestral trait (Maisonneuve et al. 2021). Phylogenetic analyses show that FLM derived from sexually monomorphic non‐mimetic ancestors (Kunte 2009, Timmermans et al.…”
mentioning
confidence: 99%
“…In line with this expectation, Su et al (2015) showed that in a mimetic butterflies where males and females mimic the same species, females are more prefect mimics than males, suggesting also that some constraints limits perfect mimicry in males. Wing pattern evolution is also shaped by developmental constraints (Van Belleghem et al 2020) that may impede divergence from the ancestral trait (Maisonneuve et al 2021). Phylogenetic analyses show that FLM derived from sexually monomorphic non-mimetic ancestors (Kunte 2009, Timmermans et al 2017 suggesting that mimicry in FLM species is associated with a costly displacement from an ancestral non-mimetic phenotype.…”
mentioning
confidence: 99%
See 2 more Smart Citations